Mapping the Ecology of China's Corporate Legal Sector: Globalization and Its Impact on Lawyers and Society. Issue 2 (1st August 2016) - LIU, Sida; TRUBEK, David M.; WILKINS, David B.
Abstract: Globalization is rapidly changing the landscape of law practice in China, especially its corporate legal sector. This article reports on the preliminary findings of the China research of the Globalization, Lawyers, and Emerging Economies (GLEE) Project—a comparative study that examines how globalization is reshaping the market for legal services in important emerging economies and how these developments are contributing to the transformation of the political economy in these countries and beyond. Adopting an ecological approach, which examines how different segments of the legal system interact with one another in complex ways, this article maps the corporate core, international linkages, and domestic contexts of China's globalizing corporate legal sector and discusses its impact on lawyers and society.